Survival of clinical stage III NSCLC according to therapeutic strategy: Relevance of the tumor board decision in the era of immunotherapy. (2022) - Benet, Justin; Toffart, Anne-Claire; Brichon, Pierre-Yves; Chollier, Thibaut; Ruckly, Stéphane; Villa, Julie; Emprou, Camille; Pierret, Thomas; Dumas, Isabelle; Ferretti, Gilbert; Moro-Sibilot, Denis; Levra, Matteo Giaj
Highlights: Treatments for stage III NSCLC include surgery, radiotherapy, and chemotherapy. Treatment by surgery led to a better survival than CT-RT. Switch from surgery to CT-RT shortened survival. The tumor board plays a key role in choosing the best strategy for stage III NSCLC. Abstract: Introduction: Stage III NSCLC comprises a heterogeneous population. Different treatment strategies are available, including surgery, radiotherapy, and chemotherapy. The PACIFIC trial results represented a significant change and improvement in the therapeutic strategy for these patients. We aimed to compare the different treatment strategies employed in Stage III NSCLC patients within our institution. Methods: All Stage III NSCLC patients discussed during the weekly thoracic oncology multidisciplinary team meetings at the University hospital Grenoble Alpes (France) between January 2010 and January 2017 were included. Patients' overall survival (OS) according to treatment strategies along with their respective changes were compared. Results: Overall, 476 patients were identified. Among patients initially scheduled to receive neoadjuvant chemotherapy followed by surgery ( n  = 60), only 37 (62%) actually underwent surgery. Median OS of the cohort was 21.3 months [IQR 25%–75%: 9.6–48.3]. Patients who received neoadjuvant chemotherapy followed by surgery displayed better survival than those treated by CT-RT: 53.2 months [IQR 25%–75%: 16.1–87.3] versus 23.9 [IQR 25%–75%, 13.3–48.1]. Survival was slightly superior for patients treated by upfront CT-RT than for those planned for neoadjuvant chemotherapy followed by surgery who eventually converted to CT-RT (concurrent or sequential): 23.9 months [IQR 25%–75%: 13.3–48.1] versus 20.4 [IQR 25%–75%:10.8–36], respectively. Conclusion: While patients who underwent neoadjuvant chemotherapy followed by surgery displayed a better survival than those treated using CT-RT, switch from surgery to CT-RT actually shortened survival. These results stress the relevance of the tumor board in deciding which is the best therapeutic strategy for Stage III disease patients.